Enhancing Students' Mathematical Understanding through Cooperative Learning at MIS Al Falah - Erna Wati; Azis Munandar (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' understanding of mathematics at MIS Al Falah through the implementation of the Cooperative Learning Model. Mathematics is a crucial subject that develops logical thinking and problem-solving skills; however, traditional teaching methods often lead to passive learning, where students are less engaged in the learning process. The Cooperative Learning Model, which emphasizes teamwork, collaboration, and peer interaction, provides an alternative approach to enhance student involvement and understanding in mathematics. The study was conducted in two cycles, involving 6th-grade students at MIS Al Falah. In each cycle, students worked in small groups to solve mathematical problems, share ideas, and support each other’s learning. The teacher acted as a facilitator, guiding the students in their discussions and ensuring that every student actively participated. Data were collected through observations, student surveys, and pre- and post-assessments to measure improvements in students' understanding, engagement, and problem-solving abilities. The findings revealed that the Cooperative Learning Model significantly improved students’ mathematical understanding. Students demonstrated better problem-solving skills, showed increased enthusiasm for the subject, and participated more actively in class discussions. The model also promoted positive interdependence among students, where they realized the value of collaboration and helping one another. This research concludes that Cooperative Learning is an effective strategy to improve mathematical understanding and foster a collaborative and supportive learning environment in the classroom.